Cooperation for Monopolization? An Empirical Analysis of Cartelization - Madhavan, Ananth N.; Masson, Robert T.; Lesser, William H. (The Review of Economics and Statistics, 1994)
Ananth N. Madhavan, Robert T. Masson, William H. Lesser, Cooperation for Monopolization? An Empirical Analysis of Cartelization, The Review of Economics and Statistics, Vol. 76, No. 1 (Feb., 1994), pp. 161-175